Flint Axe Manufacture in the Neolithic: An Experimental Investigation of a Flint Axe Manufacture Site at Hastrup V (Enget, East Zealand) - Hansen, Peter Vemming; Madsen, Bo (Journal of Danish Archaeology, 1983)
Flint Axe Manufacture in the Neolithic - An Experimental Investigation of a Flint Axe Manufacture Site at Hastrup V (Enget, East Zealand)